2010
DOI: 10.1097/mnh.0b013e328335f939
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life outcomes in chronic kidney disease

Abstract: Purpose of Review-Patients with CKD endure compromised health-related quality of life (HRQOL). Although the link between HRQOL and increased mortality in ESRD patients is welldocumented, less is known about the relationship between CKD and HRQOL. This article reviews the recent evidence on HRQOL, its correlates and proposed intervention strategies to improve HRQOL in CKD.Recent findings-A growing body of literature indicates that various co-morbid conditions related to CKD play a substantial role in the impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 53 publications
4
101
0
2
Order By: Relevance
“…QoL may be altered in patients undergoing HD, especially among different races, social relations, cultural diversity and ethnicities (17). Some studies report that it may also be associated with hemoglobin level, socioeconomic status, literacy, dialysis program, gender, comorbidities, depression and previous unsuccessful kidney transplant, as well as clinical manifestations of the disease, side effects, nutritional status and hospitalization (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…QoL may be altered in patients undergoing HD, especially among different races, social relations, cultural diversity and ethnicities (17). Some studies report that it may also be associated with hemoglobin level, socioeconomic status, literacy, dialysis program, gender, comorbidities, depression and previous unsuccessful kidney transplant, as well as clinical manifestations of the disease, side effects, nutritional status and hospitalization (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…EPO is mainly produced in the kidney after birth, and its production is severely reduced in patients with chronic kidney disease (CKD) (2) with renal anemia. The cloning of the EPO gene and the production of recombinant human EPO revolutionized the management of patients with CKD, providing an opportunity for safe long-term anemia correction, which improves cognitive function, quality of life, exercise capacity, and cardiac function (3). Nowadays, an increasing number of patients with CKD receive erythropoiesis-stimulating agents (ESAs), and annual US prescription sales for ESAs reached 10 billion dollars in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of male veterans, Hedayati et al [21] found that 21% of the sample had experienced a major depressive episode and that the prevalence of depression did not vary according to stage of CKD. Other studies have examined self-reported quality of life within the CKD population and have found that quality of life is significantly impaired in CKD patients when compared to general population norms [22,23] and that the degree of impairment is significantly associated with decline in renal function [24,25]. …”
Section: Introductionmentioning
confidence: 99%